MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA DINI MELALUI PERMAINAN BOWLING KALENG - dan Ninik Yuliani, Rosa Imani Khan (UNIVERSUM, 2016)
This study aimed to improve early childhood numeracy skills through the game of “Bowling Kaleng”. Numeracy is the ability of every child in terms of mathematics such as sort of numbers or counting and know the number. Development of children’s numeracy skills can do through the game. This would be more effective because the children’s world is playing world, one of which is the game of “Bowling Kaleng”. Research was conducted on 30 children in Group B TK Dharma Wanita Gogorante Kediri. Those aged 5 to 6 years old, consists of 16 boys and 14 girls. The method used in this study is classroom action research using two cycles. Each cycle consists of four phases: planning, action, observation and reflection. The study was conducted at the beginning of January 2016. The results of this study indicate that learning through the “Bowling Kaleng” game can improve children’s numeracy skills. The average of child’s ability to counting, add up dan reduce numbers increased to the last cycle. Through this game, children learn to count concrete objects they like in a cheerful and pleasant atmosphere.Keywords; Numeracy skills, early childhood, Bowling Kaleng game